Evaluation of Hops (Humulus iupulus) as an Antimicrobial in Broiler Diets - Cornelison, J.M.; Yan, F.; Watkins, S.E.; Rigby, Lloyd; Segal, John B.; Waldroup, P.W. (International Journal of Poultry Science, 2006)
A study was conducted to evaluate the use of hops (Humulus iupulus) in broiler diets as a potential replacement for antibiotics. Broiler diets were prepared based on nutrient specifications of top broiler companies and supplemented with either 50 g/ton penicillin or hops at 0.5, 1.0, 1.5, and 2.0 lbs/ton of feed and compared to an unsupplemented control group. Each treatment was assigned to eight replicate groups of 45 male chicks of a commercial broiler strain. The diets were fed in pelleted form with starter diets fed as crumbles. Addition of 50 g/ton of penicillin resulted in significant improvements in body weight, feed conversion, and feed efficiency at all ages, as compared to those fed the negative control. The addition of hops at 0.5 lbs per ton also resulted in significant improvements in feed conversion and feed efficiency at all ages when compared to the negative control, and also significantly improved body weight at 14 d as compared to those fed the negative control diet. At 42 d, the body weight of chicks fed 0.5 lbs of hops per ton was greater (P = 0.09) than that of chicks fed the negative control. Higher levels of hops feeding resulted in some improvements as compared to those fed the negative control; including 14 d body weight for those fed 1.0 lb per ton, and improved 1 to 42 d feed conversion and feed efficiency for those fed 1.5 lbs per ton. Results of this study suggests that inclusion of hops into diets at the rate of 0.5 lbs per ton for broiler chickens may result in improved growth rate and feed utilization in the absence of growth promoting antibiotics.